Law, culture and the figure of the girl: genre and gender violence - Rijswijk, Honni van (Routledge, 2025)
"This book argues for the critical potential of locating the girlas the subject-position and voice of legal critique. Law's imaginary is notoriously limited in its ways of thinking through and adjudicating gender violence. This book argues that 'the girl' is a key figure through which to understand, theorise and challenge law's relation to this violence. Law, Culture and the Girl explains the meaning and significance of the figure of the girl to legal, political and critical projects centred on trauma and responsibility. The book offers new readings of exemplary cultural texts that thematically deal with law's adjudication of violence against girls, emphasising the ways these texts challenge dominant ways of thinking and doing law, jurisdiction, violence, race and gender. The book also explores radical cultural figurations of the girl in fiction, films and TV series, and demonstrates the critical potential of these works in understanding and providing counter-narratives to dominant legal and cultural imaginaries. These works provide ways not only to critique existing law, but to theorise emergent forms of law-making. This book will be of interest to scholars in the areas of cultural legal studies, law and literature, feminist legal studies and cultural studies. It will also be suitable as a prescribed text for upper undergraduate classes and graduate studies in the disciplines of law, legal studies, cultural studies and criminology"--